Territórios ocupados : uma abordagem geográfica do conflito israelo-palestino através dos quadrinhos de Joe Sacco - Mendonça, Márcio José (2014)
This study looks the territorial dimension of the Israeli-Palestinian conflict from the comic journalism produced by Joe Sacco. For this, seek, preliminarily, to develop an approach to spatial representation in comics through their visual and textual language, which shows a spatial perception and expressed a range of meanings from the actions that bind the characters to their place. Within this framework of interpretation, this study focuses, through the analysis of the works of Joe Sacco, the Arab-Israeli conflict to understand the Palestinian territories occupied as a politician volume that portrays the loss of political sovereignty of the Palestinians in the broad sense. This approach emphasizes an approach to the daily lives of Palestinians through comics considering the daily occupation and their spatial dimension (ie, content that refers to the territory, since it presents a whole set of meanings that evoke a territorial sense). So the research aims to understand the occupied Palestinian territories, seeking to evidence the extent to which Joe Sacco comics provide elements for research in geography, to the extent that expresses, it is suggested, one geographicity. Such a focus, which uses the conceptual scope of geography – and notably the concept of territory and its multiples –, mediating them through the use of works of Joe Sacco, allows, we suggest a peculiar angle of approach over the territory in local conflict, to the extent that, through it, it becomes possible to observe the forms of control and territorial insecurity of Palestinians in their training territorial-space.